Metabolome and Whole-Transcriptome Analyses Reveal the Molecular Mechanisms Underlying Hypoglycemic Nutrient Metabolites Biosynthesis in Cyclocarya paliurus Leaves During Different Harvest Stages - Zheng, Xuehai; Xiao, Huibao; Chen, Jiannan; Zhu, Jinmao; Fu, Yajuan; Ouyang, Songying; Chen, Youqiang; Chen, Duo; Su, Jingqian; Xue, Ting (Frontiers in Nutrition, 2022)
Cyclocarya paliurus, a well-known nutrient and beverage plant, is under development for use in functional health care products best and natural and organic foods. We hypothesis that the composition and metabolic accumulation of hypoglycemic nutrient metabolites exhibit significant differences depending on harvest time. Therefore, it is of great significance to establish the best harvest time for C. paliurus leaves for the further development of healthy teas and other products. However, the detail compositions and molecular mechanisms of nutrients biosynthesis in C. paliurus leaves during different harvest stages remain largely unclear. Metabolome analysis showed that a suitable leaf-harvesting strategy for C. paliurus could be in September or October each year due to the high content of hypoglycemic nutrient metabolites. We found that two of the seven differentially accumulated phenolic acid metabolites have a relatively good inhibitory effect on α-amylase, indicating that they may play a role in the hypoglycemic function. Combined analysis of coexpression, ceRNA network, and weighted gene correlation network analysis (WGCNA) showed that several genes or transcription factors (TFs) in three modules correlated highly with hypoglycemic nutrient metabolites, including CpPMM, CpMan, CpFK, CpSUS, CpbglX, Cp4CL, CpHCT, and CpWRKY1. These findings help in the understanding of the molecular mechanisms and regulatory networks of the hypoglycemic nutrient metabolites in C. paliurus leaves which are dependent on harvest time and provide theoretical guidance in the development of functional health care products and foods from C. paliurus.